The pilot plant of water treatment dedicated for reducing organic matter, including selected micropollutants - Zimoch, Izabela; Mroczko, Dominik (Instal, 2021)
Constantly growing interest in micropollutants and with threats resulting from their presence in the aquatic ecosystem may result in stricter regulations related to their monitoring. This paper presents results of the preliminary micropollutants and total organics reduction effectiveness analysis, with processes alternative to classical technologies of water treatment intended for human consumption. The proposed technologies are implemented in a mobile, modular pilot plant also described in this paper. The considered processes were: coagulation, membrane filtration, sorbtion and ion exchange, and photolysis.
Keywords: coagulation; membranes; photolysis; sorbtion; ion exchange